Análisis comparativo de los estados financieros y su relación con los resultados económicos de la cooperativa de taxis san jacinto de Buena Fe, en los años, 2010-2011 - Romero Manjarrez, Sobeida Isabel (2012)
This project is working in the cooperative development of taxis "San Jacinto Good Faith", created by ministerial decision No. 001 of January 30, 1996 in the city of Buena Fe, Los Ríos province of taxis serving. Through this work is to make a general analysis of the cooperative through a horizontal and vertical analysis of financial statements, 2010-2011, with major accounts such as cash, major accounts such as cash accounts and notes payable, fixed assets and monthly partners, also applied the use of financial ratios that reveal the strengths and weaknesses. The evaluation of the cooperative financial position allowed us to know past, present and future, taking into account information from the year 2010 - 2011 the cooperative has drawn strong losses, with this analysis failed to detect the source of the weakness. It is important to note that the financial information has been very disorganized due to the constant change of the counter and that has kept this information is complete in the year mainly from 2010 to 2011.